The Influence of Product Attributes and Price Perceptions on Aqua Purchasing Decisions in East Surabaya - Fadilla Mulyasari; Siti Aminah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study investigates the impact of product features and pricing perceptions on purchasing decisions for Aqua in East Surabaya. The study was performed on Aqua consumers in the area, with a sample of 96 respondents chosen through a purposive sampling method. Data collection was conducted using an online questionnaire disseminated through Google Forms. The results indicate that product characteristics significantly impact consumer buying choices. Elements such as packaging design, product quality, and brand reputation substantially influence consumer preferences in the selection of Aqua. Moreover, price perception exerts a substantial and important influence on purchasing decisions. Consumers typically evaluate price equity, affordability, and perceived worth when making decisions. The research emphasizes that product features and pricing perceptions influence Aqua's purchasing decisions in East Surabaya. These findings offer significant insights for organizations in the bottled water sector to refine their marketing strategies by prioritizing enhancements in product qualities and refining pricing methods to meet customer expectations.